MEMBANGUN KESADARAN ENERGI TERBARUKAN DI PULAU TIDUNG: PROYEK EDUKASI UNTUK SISWA - Kasiah (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
The educational project "Building Awareness of Renewable Energy in Pulau Tidung" aims to enhance the knowledge of students and the community regarding renewable energy as an environmentally friendly alternative. Through interactive and practical learning approaches, students are introduced to various types of renewable energy, their benefits, and how to apply them in daily life. Activities include workshops, field visits, and seminars involving the community. The results of this project indicate a significant increase in student understanding, as well as their active involvement in conveying information to parents and the community. This project not only raises awareness about the importance of renewable energy but also lays the foundation for the younger generation to become environmentally conscious agents of change.